DIGITAL MOBILITY OF THE FUTURE SPECIALIST: CURRENT TRENDS - Leonov Maksym (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The article raises the issue of the mobility of social relations and individuals throughout the digital transformation period. The study aims to investigate the content and essence of the mobility phenomenon, the specifics of the expert’s professional mobility, the causes and consequences of changes in the interpretation of mobility in the context of digitalization and digital transformation of modern society; features, advantages and challenges arising in light of the expansion of digital mobility in professional and social life. The following methods were used in the research: philosophical, sociological, psychological and pedagogical analysis, synthesis of interdisciplinary approaches to the study of the content, essence and directions of development of the “mobility” category, a professiographic approach to the specification of the professional mobility concept, methods of adaptation and conceptualization to identify challenges and dangers, related to the spread of digital mobility. It has been determined that mobility is a complex interdisciplinary category that can be characterized in broad socio-economic and narrow personal contexts. It has been found out that the theory of mobility has evolved significantly in its development, expanding from the primary focus on movement between social groups to a deeper analysis of social space and various aspects of the individuals’ living. The individual’s professional mobility as a type of social mobility and such a relevant component of it as digital mobility has been emphasized. Spatial, temporal and contextual dimensions of digital mobility have been analysed. In a broad sense, digital mobility is defined as the process of digitization and integration of mobility management systems to achieve strategic goals, as well as the creation of optimized networks for more efficient information transmission. A specialist’s digital mobility is defined as the ability to work effectively and develop in a rapidly changing digital landscape including flexibility, technological competence, and openness to learning and adapting to the digital environment. The phenomenon of digital nomadism has been pointed out and briefly described as a promising model of digital mobility for the labour market in the near future. The most critical challenges associated with the widespread digital mobility to all spheres of current professional life have been identified, including digital inequality, the digital gap between generations and social groups, manipulative management of digital data, digital parkourism, digital stupidity, digital addiction, etc. To solve these and related problems, some strategies have been proposed. These are ensuring data protection and confidentiality of information in the organization and outside it; increasing the level of digital literacy among employees, forming digital competence and digital culture; establishing a balance between real and digital professional life; reducing workers’ reliance on technology by encouraging activities that do not require the use of digital devices and supporting digital awareness initiatives; developing an organization’s policies that govern the use of digital technologies, with particular attention to ethics and security. It has been concluded that there is a need to develop several measures, both at the level of the global socio-economic community and at the individual organization, which will ensure the availability of digital mobility services for those employees who experience digital alienation and/or digital divide, as well as the formation and development of a digital competence in citizens.